Non-pharmacological Management of Multiple Sclerosis: The Role of Sport and Rehabilitation - Wieczorek, Maria; Górska, Weronika; Plichtowicz, Weronika; Jaworowicz, Lena (Quality in Sport, 2025)
Introduction: Multiple sclerosis (MS) is a chronic inflammatory disease of the central nervous system that primarily affects young adults. This study aimed to review the current evidence on the role of exercise and rehabilitation in managing MS symptoms and improving patients' quality of life. Materials and Methods: A comprehensive literature search was conducted using Google Scholar and PubMed databases. The search included articles published from 2005 onwards. Keywords used in the search included "multiple sclerosis", "rehabilitation", "sport" and "therapy." Abstracts were initially screened to identify potentially relevant studies. Subsequently, each selected publication underwent thorough analysis. Objectives: The aim of this review was to collect and synthesize available information on the role of physical exercise, sports, and rehabilitation in patients with multiple sclerosis. Results: The findings highlight the significant benefits of regular physical activity and exercise for MS patients. Various forms of exercise, including aerobic training, resistance training, and water-based activities, have been shown to improve balance, mobility, fatigue levels, and overall quality of life. Emerging rehabilitation technologies, including transcranial magnetic stimulation, virtual reality, and telerehabilitation, have further expanded treatment options for MS patients. Conclusions: Exercise and rehabilitation play crucial roles in managing MS symptoms and improving patients' functional outcomes. While the evidence supports these multifaceted approaches, further research with larger cohorts is needed to establish their long-term effectiveness and refine personalized treatment protocols for MS management.